STRUKTUR KEPEMILIKAN, TATAKELOLA PERUSAHAAN, DAN KONSERVATISMA - Hellen Sanidhya Prahasita (Jurnal Akuntansi Bisnis, 2016)
This study examines the effect board independence, ownership structure (institutional ownership and managerial ownership), frequency of audit committee meetings, audit quality, and leverage on accounting conservatism in Indonesia. Samples are collected from Indonesia Stock Exchange in 2009-2013. Purposive sampling methods are employed. The data were analyzed using multiple linear regression and classical assumption for data analysis. The results that negatively affect managerial ownership and leverage conservatism positive effect on conservatism. As for the variable independence of the board of commissioners, institutional ownership, frequency of board meetings and audit quality has no effect on conservatism